Impatiens pollen germination and tube growth as a bioassay for toxic substances. - Bilderback, D E (1981)
Pollen of Impatiens sultanii Hook F. germinates and forms tubes rapidly at 25 degrees C in a simple medium containing 111.0 ppm CaCl2, 13.6 ppm KH2PO4, and 1000 ppm boric acid. Calcium, potassium, and boron are essential for germination and tube growth, but sucrose is not required. Pollen tubes grow with equal rapidity in liquid medium or on a medium solidified with 1% agar. Tube growth rates are linear for 1 hr. When different pollen sources or clonal sources are utilized, no variation in pollen tube growth is observed, and pollen from individual flowers remain viable for 26 hr. Formaldehyde inhibits pollen germination, tube production, and tube lengths at 7.5-10 ppm. With 2,4-dichlorophenol, pollen germination and tube production is inhibited at 0.5-20 ppm, while tube growth is inhibited significantly at 25 ppm. A biphasic inhibition of germination and tube formation occurs with p-cresol with a low level of inhibition occurring at 40-60 ppm and a higher one at 100-125 ppm. Tube lengths were inhibited at 150 ppm p-cresol. Acrylamide and dioctyl phthalate have no measurable effect upon pollen germination and tube growth.